The nature of red emission in porous silicon - Khomenkova, L.Yu.; Korsunska, N.E.; Bulakh, B.M.; Sheinkman, M.K.; Stara, T.R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The photoluminescence spectra of porous silicon at 77 and 300 K and their transformation during aging were investigated. The competition of two radiative recombination channels that have a common excitation mechanism was observed. It is shown that only one of them, which causes infrared emission band and is present in as-prepared samples, is connected with excitonic recombination in Si nanocrystals. The second one that causes red emission band appears during aging is supposed to be connected with carrier recombination through oxide-related defects. It is shown that this channel dominates in aged samples.